Clinical relevance of studies on the visual and radiographic methods for detecting secondary caries lesions – A systematic review. (August 2018) - Signori, Cácia; Gimenez, Thaís; Mendes, Fausto M.; Huysmans, Marie-Charlotte D.N.J.M.; Opdam, Niek J.M.; Cenci, Maximiliano S.
Abstract: Objective: Accuracy studies should associate the diagnostic criteria and outcomes collected to the treatment decision for patients to be considered clinically relevant. This systematic review performed a critical evaluation of the clinical relevance of accuracy studies on the visual and radiographic methods for secondary caries detection, and other aspects. Source: The search was conducted in PubMed, SCOPUS and ISI Web of knowledge databases. Study selection: Accuracy studies assessing clinical and/or radiographic method for evaluation of secondary caries were included. The systematization of the diagnostic criteria, lesion activity assessment and differential diagnosis of secondary caries from factors that can lead to misinterpretations were assessed. Clinical relevance was evaluated by the report of aspects related to: link to treatment decision, evaluation of patient-centered outcomes, establishment of thresholds for non-operative and operative treatment, lesion activity assessment, and reference method. Risk of bias was also assessed. A descriptive analysis was performed. Data: Following eligibility criteria, 19 articles of the 3089 searched were reviewed. Different diagnostic criteria were reported, mainly for the visual inspection. The use of a standardized diagnostic system, lesion activity assessment and differential diagnosis were described by a limited number of studies. Approximately half of the studies reported association of diagnosis and treatment. Enamel lesions were evaluated radiographically in 28.6% of studies, and visually in 69.2%. Visual diagnosis was more relevant in relation to the operative treatment decision. Patient-centered outcomes were not investigated. Conclusion: The majority of studies fails to present clinical relevance and report of patient-centered outcomes.